Survival and care practices of periviable births of <24 weeks’ gestation—a single center retrospective study in China, 2015–2021 - Chen, Chun; Xiong, Xiaoyun; Zhao, Jie; Wang, Meiqi; Huang, Zhifeng; Yang, Chuanzhong (Frontiers in Pediatrics, 2022)
Background Data from the China Neonatal Network currently shows that the survival rate of very preterm infants in China has improved in recent years. However, due to the unequal economic and medical development of each city in China, the national data do not completely represent the level of neonatal care in the metropolitan areas. Though many studies have published their short- or long-term survival, very few have described the care practices and the course of stay of these neonates in detail. Our objective was to examine the survival and clinical practices among preterm infants born at <24 weeks’ gestational age (GA) in a high-income city in China, from 2015 to 2021. Methods Retrospective study of preterm infants <24 weeks GA in a level 3 neonatal intensive care unit in China, over a period of 7 years (2015–2021). Care practices in neonatal intensive care units (NICU) and short- and long-term survival were measured. Results A total of 32 periviable infants were included, with a median GA of 23.0 weeks and mean (SD) birth weight of 497 (94) g; 17 infants (53.1%) were female. While none of the infants born at 21 weeks of gestation survived until discharge, the survival rates were 25.0% (3 of 12) for infants born at 22 weeks and 58.8% (10 of 17) at 23 weeks. Antenatal corticosteroids were used in 56.3%, and 100% were vaginal birth. In the delivery room, surfactant was prescribed for 46.9% of the infants, and postnatal dexamethasone (≥2 courses) was prescribed to 61.5% of the infants. Logistic regression analysis showed that Apgar score at 5 minutes (OR = 2.007, 95% CI, 1.031 to 3.906, P < 0.05) increased the risk of death, while the increase in gestational age (OR = 0.238, 95% CI, 0.060–0.936, P < 0.05), antenatal use of steroids (OR = 0.287, 95% CI, 0.106–0.778, P < 0.01), and premature rupture of membranes (OR = 0.141, 95% CI, 0.024 −0.847, P = 0.032) could decrease the risk. No or mild neurodevelopmental impairment in surviving infants was 76.9% (10 of 13). Conclusions Although the survival rate of periviable infants was shown to be improved in our study, there is still much room for improvement, and active follow-up information should be conducted.